MEASUREMENT OF TOTAL AND PARTIAL PHOTON PROTON CROSS-SECTIONS AT 180 GEV CENTER-OF-MASS ENERGY - Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Schlereth, J; Stanek, R; Talaga, R; Thron, J; Arzarello, F; Ayad, R; Bari, G; et al. (1994)
Photon proton cross sections for elastic light vector meson production, σel νp, inelastic diffractive production, σnd νp, non-diffractive production, σd νp, as well as the total cross section, σtot νp, have been measured at an average υp center of mass energy of 180 GeV with the ZEUS detector at HERA. The resulting values are σel νp = 18 ± 7 μb, σd νp = 33 ± 8 μb, σnd νp = 91 ± 11 μb, and σtot νp 143 ± 17 μb, where the errors include statistical and systematic errors added in quadrature. © 1994 Springer-Verlag.